2019
DOI: 10.1088/1361-6439/ab034d
|View full text |Cite
|
Sign up to set email alerts
|

The key role of suppressor diffusion in defect-free filling of the through-silicon-via with high depth

Abstract: Defect-free filling of through-silicon-via (TSV) with high depth is still a challenge to obtain in the industry. Herein, physical quantities, i.e. deposited copper morphology, local current density, local coverage of additives and local concentrations of additives, were investigated in the filling process of TSV with high depth. It was found that the local current density was controlled by the local coverage of accelerator. And the competitive adsorption process of additives was dominated by the suppressor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The transport performance of CTAB, PEG, and JGB were also analyzed using an electrochemical test, equivalent to that of Wang. 15 As no electrolyte stirring was used in this study, the transport of CTAB in the micro via was mainly determined through diffusion and migration. 16 The results showed that CTAB was transported faster than JGB and PEG.…”
Section: Resultsmentioning
confidence: 99%
“…The transport performance of CTAB, PEG, and JGB were also analyzed using an electrochemical test, equivalent to that of Wang. 15 As no electrolyte stirring was used in this study, the transport of CTAB in the micro via was mainly determined through diffusion and migration. 16 The results showed that CTAB was transported faster than JGB and PEG.…”
Section: Resultsmentioning
confidence: 99%
“…This causes the uniform deposition rate of plating. As shown in figure 9(c), at high current density conditions, the suppressor is depleted in the middle of via due to the consumption cannot be replenished in time by the diffusion [23,24]. Above the suppressor exhaustion depth, the accelerator coverage increases with the decreasing of the suppressor concentration.…”
Section: Tsv Filling Patterns Affected By the Current Densitymentioning
confidence: 95%
“…According to convection-dependent adsorption (CDA) effect, forced convection enhances the concentration of chloride ions on the cathode surface, thereby promoting the adsorption of suppressor [22], [23]. On the other hand, the limited diffusion of suppressor is the key factor causing the void defect of deep TSV filling [14]. Although forced convection cannot reach the bottom of the deep via, it increases the concentration gradient in the via and promotes the diffusion of the suppressor to the bottom of the via [24].…”
Section: Forced Convection Promotes the Adsorption Of Suppressormentioning
confidence: 99%
“…However, with the increase of TSV depth, the mass transfer of additives inside via is limited. Therefore, the consumption of additives cannot be replenished in time, resulting in defects [13], [14]. To promote the mass transfer of additives, pause pulse current and forced convection are often applied [15]- [21].…”
Section: Introductionmentioning
confidence: 99%